WHAT-IF ANALYSIS DENGAN EXCEL SCENARIO MANAGER UNTUK PERHITUNGAN NERACA, LAPORAN LABA RUGI DAN ANALISA RASIO KEUANGAN PERUSAHAAN - Hoki Cahyadi Nugroho (Bina Ekonomi, 2008)
Excel's Scenario Manager Feature makes automating your what-if models easy. You can store different sets of input values (known as changing cells) for any number of variables and give a name to each set. You can then select a set of values by name, and Excel displays the worksheet by using those values. You can generate a summary report that shows the effect of various combinations of values on any number of result cells. The summary report can be an outline or a pivot Table.